2014
DOI: 10.4103/1119-3077.130247
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome among children in Kano: A clinicopathological study

Abstract: Focal segmental glomerulosclerosis was the most common histological subtype diagnosed in Kano among children with nephrotic syndrome in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 20 publications
(59 reference statements)
7
22
4
Order By: Relevance
“…This is consistent with previous studies in our centre, which showed high rates of steroid responsiveness since the steroid-responsive patients may become steroid dependent [10]. In contrast, similar studies conducted in Ibadan and Kano, Nigeria, and those in India and Greece, showed a preponderance of SRNS over SDNS [4,13,14,17]. In France, Finland and Italy, the commonest indication is asymptomatic urinary abnormalities [18].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with previous studies in our centre, which showed high rates of steroid responsiveness since the steroid-responsive patients may become steroid dependent [10]. In contrast, similar studies conducted in Ibadan and Kano, Nigeria, and those in India and Greece, showed a preponderance of SRNS over SDNS [4,13,14,17]. In France, Finland and Italy, the commonest indication is asymptomatic urinary abnormalities [18].…”
Section: Discussionsupporting
confidence: 91%
“…FSGS and MCD were common diagnoses in our study. The high incidence of FSGS is consistent with previous reports from our centre and other centres in Nigeria [10,13,14,16]. However, previous Nigerian studies reported a low incidence of MCD [21,22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…From reports of studies carried out in our locale, although the cohorts are not large [14, 39] and various other parts of the world, FSGS either ranks first or second as the most common cause of idiopathic steroid resistant NS [40–42]. …”
Section: Discussionmentioning
confidence: 99%